THE EFFECT OF THE PROBLEM BASED LEARNING MODEL, AUDIO VISUAL MEDIA AND SCHOOL ENVIRONMENT ON STUDENTS' MOTIVATION TO LEARN SOCIAL SCIENCES AT SDN BANTARAN 1 - Yunita, Astrie; Sri Hariani, Lilik; Fauzia Putra, Dwi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the influence of Problem Based Learning (PBL), audiovisual media, and school environment on students' learning motivation in Social Studies (IPS) at SDN Bantaran 1. Specifically, it investigates the partial and simultaneous effects of the three independent variables on students' learning motivation. The research employed a quantitative approach with an explanatory research design. The population consisted of all fourth, fifth, and sixth grade students at SDN Bantaran 1, totaling 77 students, who were also used as the research sample (saturated sampling). Data collection was conducted using a Likert-scale questionnaire that has been tested for validity and reliability. The data were analyzed using descriptive statistics and multiple linear regression, including t-test, F-test, and the coefficient of determination (R²), with the assistance of SPSS software. The results showed that only the school environment variable had a significant positive effect on learning motivation (Sig. = 0.002 < 0.05). In contrast, Problem Based Learning and audiovisual media did not show a significant partial effect. However, all three variables together had a significant simultaneous effect on learning motivation (F = 9.045, Sig. = 0.000). The coefficient of determination (R²) was 0.271, indicating that 27.1% of the variation in learning motivation could be explained by the three independent variables. These findings suggest that the school environment plays a more dominant role in shaping students' learning motivation, compared to the applied learning model and media used .